Bus Priority Hardware-in-the-loop Simulation System Based on SUMO - Zeng, Xiaoqiang; Wu, Juyuan; Wang, Sen; Zhang, Xucai; Ding, Hailong (2023 5th International Conference on Frontiers Technology of Information and Computer (ICFTIC), 2023)
There are two main ways to verify traffic signal control algorithms currently, one is to verify algorithm through the API interface of micro traffic simulation software, another is to operate and test directly in real road scenarios. The former lacks verification of the algorithm carrier environment adaptability, while the latter exists significant security risks. In this paper, hardware-in-the-loop simulation system based on the open-source micro traffic simulation software SUMO is built. Relying on this system, comparative verification before and after the priority operation of two-route bus under the background scheme of fixed cycle and induction control was conducted. The system effectively output indicators such as the number of stops and delay data of public and social vehicles. The experimental data shows that the delay reduction rates of public transportation vehicles under the background of fixed cycle and induction control respectively reach 53.29% and 36.62%, while has almost no effect on the parking frequency of social vehicles. The results indicate that both fixed cycle and induction control backgrounds are suitable for running bus priority algorithms, which is of great significance for urban road traffic management.